Cultural politics in Polybius's Histories - Champion, Craige Brian (Hellenistic culture and society, 2004)
Polybius has provided us with the earliest continuous narrative of the rise of the Roman Empire. Champion shows how Polybius tailored his work for a number of audiences, both his fellow Greeks & the Roman conquerors, affording new insights into a work whose subtlety & complexity have gone largely unrecognised.